The 3rd grade students’ perception on learning CLIL through Cambridge's Guess What Textbook: A pilot study - Chatarina Tri Rahmawati; Nunung Suryati; M Misbahul Amri; Lestari Setyowati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
Content and Language Integrated Learning (CLIL) offers a strategic approach to developing students’ English language proficiency and knowledge of other areas. Originally popular in European learning settings, CLIL has recently gained attention in the Indonesian EFL context. This study examines how 3rd-grade students perceive learning using CLIL through the Cambridge textbook Guess What. A quantitative approach was used with 66 third-grade students in a private Catholic elementary school. They filled out a questionnaire that assessed engagement, subject comprehension, and language development. Descriptive statistical analysis was used to identify key trends in student responses. It was found that students enjoyed CLIL-based learning and demonstrated increased engagement. Another thing was that most of the students only felt that their English speaking was developed through CLIL, yet they did not feel the same way about their writing and reading skills. However, while CLIL facilitated better comprehension of other subjects, many students questioned the necessity of learning non-language subjects in their English class. Through the findings, this study will shed light on EFL practices in Indonesia by highlighting CLIL’s benefits and challenges at the primary level. It emphasizes the need for targeted strategies to support reading and writing, alongside teacher training to maximize CLIL’s effectiveness.